A NH2-HLB composite adsorption membrane for adsorbing organic phosphates and its preparation method and application
By using the NH2-HLB composite adsorption film to detect organic phosphate in the DGT device, the existing technology is difficult to reflect the problem of the effectiveness of organic phosphate biosenophilia and the cost of adsorption materials, and achieve efficient and low-cost organic phosphate ester. Adsorption and detection effect.
Patent Information
- Application Number
- CN202410822974.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-24
AI Technical Summary
The existing DGT technology is difficult to truly and effectively reflect the bioavailability of organophosphate in the environment, and the existing adsorption materials are expensive, making it difficult to achieve efficient and low-cost organophosphate adsorption.
The NH2-HLB composite adsorption membrane is used. The membrane is mixed with the quality ratio of HLB resin and NH2 silicone in the activated methanol, and the agarose solution is added to the agarose solution to detect the organic phosphoric acid ester in the DGT device.
It achieves efficient adsorption of organic phosphates TBEP, TCPP and TPhP, has high biological effectiveness and sensitivity, is suitable for different environmental conditions, and has low cost.
Smart Images

Figure CN118767888B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of DGT, and in particular to an NH2-HLB composite adsorption membrane for adsorbing organic phosphate, and a preparation method and application thereof. Background Art
[0002] Organophosphate esters (OPEs) are phosphoric acid derivatives containing carbon-phosphorus bonds or organic groups. OPEs are usually added to materials physically rather than through chemical bonding, so they are easily released into the surrounding environment through volatilization, abrasion and leaching. OPEs can be transferred and transformed at the soil-air, soil-water and soil-plant interfaces, and soil is an important source and sink of OPEs. Organophosphate esters can be divided into halogenated alkyl, non-halogenated alkyl and aromatic groups according to the different substituent groups. They have certain biological toxicity, such as endocrine disruption, neurotoxicity or oxidative damage. OPEs are also related to obesity, changes in sex hormone levels, chronic kidney disease and the development of adverse behaviors. In particular, halogenated OPEs are also carcinogenic.
[0003] Therefore, the migration and transformation behavior of organophosphates in the environment has been paid attention to in recent years, and it is necessary to predict the content of organophosphates in the environment. However, the existing traditional prediction methods cannot truly and effectively reflect the bioavailability of organophosphates. Diffusive Gradients in Thin-films (DGT), based on Fick's first diffusion law, is mainly used to in situ determine the effective state content of target objects in natural environments. DGT technology can predict the effective state content of target objects, simulate the absorption process of organisms to specific target objects in environmental media such as water, soil or sediment, and thus estimate the kinetic parameters in the dynamic process, which plays a very important role in the dynamic process of pollutants in environmental media. Compared with traditional methods, the measurement results of DGT technology are not affected by soil properties and show a higher correlation coefficient with the content of target pollutants inside plants. Therefore, it has more advantages in evaluating the bioavailability of organophosphates in different types of soils.
[0004] The DGT device consists of four parts: the outer shell, the filter membrane, the diffusion phase and the binding phase. The outer shell plays the role of a fixed membrane. The filter membrane can filter out interfering substances in the environmental medium, such as dust, soil and other particulate matter, to avoid affecting the measurement results of the DGT device. The diffusion phase is a component of the free diffusion of ions, which controls the entire diffusion process and creates the necessary conditions for the entire diffusion process. The core of the DGT device is the binding phase, which can quickly combine with the target, so that the concentration of the target is greatly reduced between the diffusion phase and the binding phase, forming a concentration gradient. When the internal and external concentrations are close to each other, equilibrium is reached, that is, the sampling is completed, and then the substances on the adsorption membrane are eluted for quantitative determination. At present, DGT technology has been widely used in the determination of the bioavailability of heavy metal elements in water, sediments and soil, and has achieved good results. However, there has been no research report on the use of DGT technology in the analysis of the free dissolved concentration of organic phosphates in the environment.
[0005] At present, research on organophosphate adsorption materials is very limited. The materials for adsorbing organophosphates in existing commonly used DGT devices are mainly commercially available LSLD-AT DGT devices, but they are expensive. Therefore, in order to make the in-situ passive sampling of organophosphates using DGT devices more practical, it is urgent to provide a material with high adsorption efficiency, low cost, and the ability to specifically adsorb organophosphates and its DGT device. Therefore, the present invention proposes an NH2-HLB composite adsorption membrane for adsorbing organophosphates, a preparation method thereof, and an application in detecting the concentration of organophosphates in the environment in a DGT detection device. Summary of the invention
[0006] The purpose of the present invention is to provide an NH2-HLB composite adsorption membrane for adsorbing organic phosphates and a preparation method and application thereof, so as to solve the problem that the total amount of organic phosphates in the environment cannot truly and effectively reflect the biological effectiveness of organic phosphates.
[0007] To achieve the above objectives, the present invention provides an NH2-HLB composite adsorption membrane for adsorbing organic phosphates. The NH2-HLB composite adsorption membrane is prepared by adding a polymer formed by HLB resin activated by methanol and NH2 silica gel in a mass ratio of 6:4 to an agarose solution.
[0008] The present invention also provides a method for preparing the above-mentioned NH2-HLB composite adsorption membrane for adsorbing organic phosphate, comprising the following steps:
[0009] (1) soaking the HLB resin in a methanol solvent for 30 minutes, washing with ultrapure water after solid-liquid separation, and obtaining a methanol-activated HLB resin;
[0010] (2) soaking the NH2 silica gel in a methanol solvent for 30 minutes, and washing with ultrapure water after solid-liquid separation to obtain NH2 silica gel activated by methanol;
[0011] (3) mixing the methanol-activated HLB resin with the methanol-activated NH2 silica gel to obtain an adsorption material;
[0012] (4) mixing the adsorption material, agarose powder and ultrapure water, and heating to prepare an agarose solution;
[0013] (5) The agarose solution was injected into the gap of a glass plate containing a 0.5 mm U-shaped Teflon sheet and solidified into a film to obtain an NH2-HLB composite adsorption film.
[0014] Preferably, in step (1), the mass volume ratio of HLB resin to methanol solvent is 4.5 g:6.3 mL.
[0015] Preferably, in step (2), the mass volume ratio of NH2 silica gel to methanol solvent is 3g:4.2mL.
[0016] Preferably, in step (3), the mass ratio of methanol-activated HLB resin to methanol-activated NH2 silica gel in the adsorption material is 6g:4g.
[0017] Preferably, in step (4), the mass volume ratio of the adsorption material, agarose powder and ultrapure water is 70g:10g:500mL.
[0018] Preferably, in step (5), the film-forming temperature is 20±5° C., and the film-forming time is ≥60 min.
[0019] The present invention also provides an application of the above-mentioned NH2-HLB composite adsorption membrane for adsorbing organic phosphates, wherein the NH2-HLB composite adsorption membrane is used in a DGT device to detect the concentration of organic phosphates in the environment.
[0020] Preferably, the organic phosphate is one of TBEP, TCPP and TPhP.
[0021] Therefore, the present invention provides an NH2-HLB composite adsorption membrane for adsorbing organic phosphates and a preparation method and application thereof, which have the following beneficial effects:
[0022] (1) The NH2-HLB composite adsorption membrane prepared by the present invention can simultaneously fix a mixed solution of organic phosphates TBEP, TCPP and TPhP, and the adsorption effect is more biologically effective;
[0023] (2) In the DGT device assembled using the NH2-HLB composite adsorption membrane prepared in the present invention, the saturated adsorption capacity of the NH2-HLB composite adsorption membrane for TBEP, TCPP and TPhP is 81.53 μg / cm 2 、74.69μg / cm 2 and 77.84 μg / cm 2 , and the effective adsorption capacity was 0.709 μg / cm 2 , 0.661μg / cm 2 and 0.552 μg / cm 2 ;
[0024] (3) The effective adsorption capacity of the NH2-HLB composite adsorption membrane prepared by the present invention is relatively high, which is conducive to the long-term deployment of the NH2-HLB composite adsorption membrane for sampling. The NH2-HLB composite adsorption membrane has a sufficiently large adsorption capacity, is suitable for most organic phosphate pollution levels in environmental media, and has high sensitivity.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a structural schematic diagram of the DGT device;
[0027] Figure 2 This is a scanning electron microscope image of the NH2-HLB composite adsorption film prepared in an embodiment of the present invention;
[0028] Figure 3 The bar graph is a graph showing the adsorption capacity of TBEP, TCPP and TPhP by the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention;
[0029] Figure 4 The figure is a fitted straight line graph showing the enrichment quality of the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention as a function of the concentrations of TBEP, TCPP and TPhP;
[0030] Figure 5 It is a fitting curve diagram of the adsorption kinetics of TBEP, TCPP and TPhP by the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention;
[0031] Figure 6 The first-order kinetic fitting curve diagram of the adsorption of TBEP, TCPP and TPhP by the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention;
[0032] Figure 7 The second-order kinetic fitting curve diagram of the adsorption of TBEP, TCPP and TPhP by the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention;
[0033] Figure 8 The adsorption performance diagram of the DGT device assembled with the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention at different pH values;
[0034] Fig. 9 The adsorption performance diagram of the DGT device assembled using the NH2-HLB composite adsorption membrane prepared in the embodiment of the present invention under different ionic strengths;
[0035] Fig.10 This is a graph showing the adsorption performance of a DGT device assembled using the NH2-HLB composite adsorption membrane prepared in an embodiment of the present invention at different DOM concentrations;
[0036] Figure Number:
[0037] 1-1 outer shell, 1-2 base, 2 filter membrane, 3 diffusion phase, 4 binding phase. DETAILED DESCRIPTION
[0038] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects of the present application, the following is a detailed description in combination with the specific embodiments listed and the accompanying drawings. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and the scope of protection of the present application cannot be limited by this. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in this application, as long as there is no technical contradiction or conflict, the various technical features mentioned in each embodiment can be combined in any way to form a corresponding implementable technical solution.
[0040] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0041] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.
[0042] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are the reagents, instruments, and equipment commonly used by technicians in this field. "TBEP" refers to tris(butoxyethyl) phosphate; "TCPP" refers to tris(2-chloropropyl) phosphate; "TPhP" refers to triphenyl phosphate; "DGT" refers to thin film gradient diffusion technology; "HLB" refers to HLB resin; "NH2" refers to amino silica gel;
[0043] The DGT device used in the present invention is as follows Figure 1 As shown, 1-1 shell, 1-2 base, 2 filter membrane, 3 diffusion phase, 4 binding phase, the shell and base are both made of ABS, the diffusion phase (membrane) material is agarose gel, thickness: 0.8mm, diameter: 2.5cm; the filter membrane is PTFE (polytetrafluoroethylene), thickness: 0.14mm, diameter: 2.5cm, pore size: 0.45μm; the binding phase (equivalent to the NH2-HLB composite adsorption membrane prepared in this application) has a thickness of 0.5mm and a diameter of 2.5cm.
[0044] Example
[0045] This embodiment provides a method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphates, and the specific steps are as follows:
[0046] Add 4.5g of HLB resin to 6.3mL of methanol solvent, add 3g of NH2 (amino) silica gel to 4.2mL of methanol solvent, soak for 30min, centrifuge at 7200rpm for 5min, remove the supernatant, retain the deposited solid at the bottom and wash with ultrapure water. Add the solid to ultrapure water and shake, centrifuge at 7200rpm for 5min, remove the supernatant, repeat the ultrapure water washing three times, and finally obtain HLB resin and amino silica gel activated by methanol; finally, add ultrapure water to the activated resin, keep the liquid level above the resin and store it. When taking, the remaining sediment weighed after pouring the upper clear liquid is the wet weight.
[0047] When preparing the binding membrane of NH2-HLB resin, the mass ratio of NH2 silica gel to HLB resin is 4 to 6, and the particle size of the two substances does not exceed 60μm. In the process of preparing the binding phase, 10g of agar powder, 70g of wet weight of adsorption material, and 500mL of ultrapure water are weighed, mixed evenly and heated to prepare an agar solution. Subsequently, the agar solution is injected into the gap between the glass plates, which contains a 0.5mm thick U-shaped Teflon sheet to ensure that the solution is evenly distributed and does not contain bubbles. Then, the glass plates are placed in a horizontal position and cooled at room temperature for 60min to allow the solution to solidify and finally form an adsorption membrane. After the solution is completely solidified, the fixing clamp is removed and the NH2-HLB film is gently removed from the glass layer. Subsequently, the NH2-HLB film is cut into circular sheets with a diameter of 25mm as the NH2-HLB binding membrane. To ensure the stability and activity of the binding membrane, it was immersed in a 0.01 mol / L NaCl solution and stored in a refrigerator at 4°C for subsequent use.
[0048] Performance Verification:
[0049] 1. In order to explore the microstructure and chemical properties of the synthetic material, the present invention uses scanning electron microscopy (SEM) characterization to analyze the NH2-HLB composite adsorption material obtained in Example 1.
[0050] Figure 2 The scanning electron microscope image of the NH2-HLB composite adsorbent clearly shows the surface morphology of the combined phase. Figure 2 It can be seen that it is spherical in shape, and the HLB resin and the amino resin have different particle sizes, which significantly increases the specific surface area of the composite material, thereby exposing more binding sites, helping to increase the adsorption capacity of the target, ensuring excellent adsorption performance, and effectively avoiding the reduction in DGT technology detection accuracy due to local lack of adsorption particles.
[0051] 2. In order to comprehensively evaluate the applicability of the adsorption membrane as a binding phase in the DGT device, especially its adsorption capacity for specific targets, this experiment conducted an in-depth study on the interaction between NH2-HLB composite adsorption membrane and organophosphates.
[0052] The adsorption membrane was placed in a 20 mL 1000 μg / L OPEs mixed solution of three organophosphates, TBEP, TCPP and TPhP, and the actual adsorption process was simulated by continuous oscillation for 24 hours. To ensure the accuracy and reliability of the experimental data, three sets of parallel experiments were conducted, and the concentration changes of the target organophosphates before and after oscillation were accurately measured.
[0053] Figure 3The results show that the saturated adsorption capacity of the NH2-HLB composite adsorption membrane for TCPP and TPhP is 18.32μg and 19.09μg respectively, and the saturated adsorption capacity for TCPP is at least 20.00μg. That is, the saturated adsorption capacity of the NH2-HLB composite adsorption membrane for the three organic phosphates TBEP, TCPP and TPhP is 81.53μg / cm 2 、74.69μg / cm 2 and 77.84 μg / cm 2 .
[0054] 3. In order to explore the effective adsorption capacity of the DGT device, the DGT device was placed in a 2.5L mixed solution of TBEP, TCPP and TPhP with 0.01M NaCl and the concentrations were 10, 100, 200, 500, 1000 and 2000μg / L, respectively, and kept under continuous stirring for 24 hours. After the experiment, the DGT device was taken out and the OPEs on the adsorption membrane were eluted by standard methods for subsequent quantitative analysis. The adsorption performance of the DGT device in OPEs solutions of different concentrations was explored.
[0055] like Figure 4 As shown in the figure, as the concentrations of TBEP, TCPP and TPhP in the solution gradually increased from 0 to 200 μg / L, the mass of organophosphate on the binding phase was linearly positively correlated with the solution concentration. This result shows that within this concentration range, there are still a large number of adsorption sites in the binding phase, which are sufficient to meet further adsorption needs. However, when the solution concentration of organophosphate continues to increase, the growth of adsorption mass gradually deviates from the theoretical expected value, which indicates that the available adsorption sites of the binding phase are decreasing and gradually approaching saturation. Therefore, the mass of TBEP adsorbed by the binding phase when the TBEP concentration is 200 μg / L is selected as the effective adsorption capacity of the NH2-HLB binding phase, which is 0.71 μg / cm 2 Based on the same method, the effective adsorption capacity of NH2-HLB combined with TCPP and TPhP was determined to be 0.66 μg / cm 2 and 0.55 μg / cm 2 .
[0056] 4. The adsorption behavior of NH2-HLB binding phase on TBEP, TCPP and TPhP was investigated by studying the adsorption gel through kinetic experiments. The HLB and amino silica gel adsorption films were placed in a glass sample bottle containing 500 mL of OPEs solution with a concentration of 200 μg / L. Make sure that the NH2-HLB binding film is completely immersed in the solution, and place it in a constant temperature shaker, and take out samples at different time intervals (5min, 15min, 30min, 60min, 2h, 4h). Set the shaker temperature to 30°C and the speed to 200rpm. To ensure the accuracy and reliability of the data, three parallel samples were set for each time gradient. The concentrations in the solution before and after the adsorption of the NH2-HLB binding phase were measured respectively, and the mass of the adsorbed OPEs was obtained by calculating the difference between the initial concentration and the residual concentration and multiplying it by the volume of the solution (20mL).
[0057] The experimental results are as follows Figure 5 As shown in the figure, when the initial concentration of TBEP, TCPP and TPhP was 200 μg / L, the new combination phase showed a faster adsorption rate in the initial stage. For TBEP, the experimental data showed that within the first 5 minutes, its average adsorption rate was as high as 89.01 ng / min / cm 2 , then dropped to 11.75ng / min / cm at 60min 2 , that is, the adsorption rate gradually slowed down and finally reached a stable state; the average adsorption rate of TCPP in the first 5 minutes was 63.273ng / min / cm 2 , and dropped to 11.92ng / min / cm within 60min 2 The adsorption rate then continued to slow down and eventually reached saturation. For TPhP, the experimental results showed that the average adsorption rate in the first 5 minutes reached 158.66 ng / min / cm 2 , and dropped to 52.94ng / min / cm at 15min 2 As time goes by, the adsorption rate gradually slows down and reaches equilibrium. Compared with the adsorption performance of HLB-DGT device in OPEs solution in previous studies, the first 30 min showed linear adsorption, and the adsorption rates of TBEP, TCPP and TPhP were 1.55, 2.20 and 2.06 ng / min / cm, respectively. 2 , which is much lower than the adsorption rate of the NH2-HLB binding phase DGT. This result shows that the new binding phase has excellent performance in the rapid adsorption of TBEP, TCPP and TPhP.
[0058] In addition, the adsorption rate of organic phosphates on the adsorption film was determined according to the pseudo-first-order kinetic model and the pseudo-second-order kinetic model.
[0059] The specific model equation is as follows:
[0060] Pseudo-first-order kinetic model equation:
[0061] q e -q t =lnq e -k1t(1)
[0062] Pseudo-second-order kinetic model equation:
[0063]
[0064] In the formula, q e represents the adsorption amount at the equilibrium moment, the unit is μg / g, that is, the mass of organic phosphate adsorbed per unit mass of adsorption membrane; q t Represents the adsorption amount at time t, the unit is μg / g.
[0065] k1 and k2 represent the constants of reaction kinetics, and the units are 1 / min and g / mg / min.
[0066] Depend on Figure 6 and Figure 7 The curve of the fitting equation was obtained, and the fitting parameters of the two were compared. The first-order fitting correlation R of the NH2-HLB composite adsorption membrane for the three organic phosphates TBEP, TCPP and TPhP was 2 are 0.839, 0.929 and 0.999; the secondary fitting correlation R 2 are 0.917, 0.949 and 0.999. After comparative analysis, the second-order fitting equation shows a more superior effect in describing the adsorption process, and can more accurately reflect the actual situation compared with the first-order fitting equation. Therefore, it is more appropriate to use the quasi-second-order fitting equation to describe the adsorption kinetics of TBEP, TCPP and TPhP by NH2-HLB composite adsorption membrane. This result shows that the adsorption of TBEP, TCPP and TPhP by NH2-HLB composite adsorption membrane is mainly chemical adsorption, which further verifies the mechanism of the adsorption process.
[0067] 5. Performance test of DGT device (adsorption material performance test)
[0068] In order to evaluate the performance of DGT assembled by using the NH2-HLB composite adsorption membrane prepared by the present invention under different environmental conditions (the device comprises a 0.5 mm NH2-HLB resin adsorption membrane, a 0.8 mm agarose diffusion gel and a 0.14 mm PTFE filter membrane). These DGT devices were placed in 2 L of fully stirred 20 μg / L TBEP, TCPP and TPhP solutions, respectively, and the solution conditions included different pH values, ionic strengths (IS) and dissolved organic matter (DOM) contents. The specific experimental conditions are as follows: First, under the conditions of IS of 0.01MNaCl and DOM of 0mg / L, experiments with pH values of 4, 5, 7 and 9 were set up; secondly, under the conditions of pH of 6±0.5 and DOM of 0mg / L, the effects of IS of 0.0001, 0.001, 0.01, 0.1 and 1M on the performance of DGT were investigated; finally, under the conditions of pH of 6±0.5 and IS of 0.01MNaCl, the effects of changes in DOM content of 2mg / L, 5mg / L, 10mg / L and 20mg / L on the performance of DGT were investigated.
[0069] (1) Effect of different pH conditions
[0070] Take several beakers containing 4L of OPEs solution with a concentration of 20μg / L, control the sodium chloride concentration to 0.01mol / L, and use hydrochloric acid and sodium hydroxide solutions to accurately adjust the pH value of the solution in each beaker to ensure that it is within the set range of 4, 5, 7 and 9. Under each pH condition, three NH2-HLB-DGT devices were deployed to perform three sets of parallel experiments. To ensure sufficient mixing and interaction of the components in the solution, the solution was stirred continuously for 24 hours using a mechanical stirrer. After stirring, the NH2-HLB-bound phase DGT device was removed and thoroughly cleaned with ultrapure water to remove surface residues. Open the DGT shell and use clean tweezers to separate the bound membrane and the diffusion membrane. The separated bound membrane was placed in a glass sample bottle for subsequent elution treatment and analysis.
[0071] The adsorption effect of NH2-HLB on TBEP, TCPP and TPhP in the pH range of 4.0 to 9.0. Figure 8 The results shown in Figure 2 show that when the pH value of the initial solution is between 4.0 and 9.0, the ratio of the TBEP concentration measured by the NH2-HLB binding phase to the solution concentration (C DGT / C soln ) was maintained between 0.87 and 0.99; for TCPP, the concentration ratio was maintained between 0.852 and 0.9985; and for TPhP, the concentration ratio was between 0.86 and 0.99. The consistency of these values indicates that within the pH range of 4.0 to 9.0, C DGT / C soln The value is always stable between 0.85 and 1.00. Therefore, in the pH range of 4-9, the adsorption process of TBEP, TCPP and TPhP by NH2-HLB binding phase is not affected by pH value, that is, NH2-HLB binding phase DGT technology has a certain tolerance in the determination of organophosphates and is suitable for environmental conditions with different pH values.
[0072] (2) Effect of different ionic strengths
[0073] A mixed solution of TBEP, TCPP and TPhP with a concentration of 20 μg / L was prepared, the pH of the solution was adjusted to be maintained within the range of 6.0±0.5, and multiple ionic strength gradients were set, specifically 0.0001, 0.001, 0.01, 0.1 and 1 mol / L sodium chloride (NaCl) solutions. Three HLB-type diffusion gradient technology (DGT) devices were placed in the solution under each ionic strength condition, and the solution was uniformly stirred for 24 hours using a mechanical stirrer. The HLB adsorption membrane was removed from the DGT device, ultrasonically eluted, and the eluted liquid was subjected to quantitative analysis of the concentration of organic phosphates.
[0074] The experimental results show that Fig. 9 , under different ionic strengths, the ratios of the values of TBEP, TCPP and TPhP measured by the prepared DGT to the concentrations in the solution were 0.81 to 0.99, 0.77 to 0.97 and 0.80 to 0.93, respectively. It can be seen that within the ionic strength range set in this study, C DGT / C soln The value is always maintained between 0.9 and 1.1, which indicates that the adsorption of TBEP, TCPP and TPhP on NH2-HLB composite adsorption membrane is not affected by ionic strength.
[0075] (3) Effect of DOM concentration
[0076] To determine the adsorption behavior of OPEs at different DOM concentrations, 5 L of a mixed solution of TBEP, TCPP and TPhP containing 0.01 mol / L NaCl was prepared, and the concentration was set to 20 μg / L. To ensure the consistency of experimental conditions, the pH value of all solutions was adjusted to 6.0 ± 0.5. The concentration of DOM was set at four levels of 2, 5, 10 and 20 mg / L. At each set DOM concentration, three HLB-DGT devices were used for experiments. The device was placed in the corresponding beaker, and the solution was stirred continuously for 24 hours using a mechanical stirrer to ensure sufficient contact and adsorption. After the stirring was completed, the HLB-bound membrane in the device was removed and ultrasonic elution was performed to release the adsorbed TBEP, TCPP and TPhP. Finally, the concentrations of TBEP, TCPP and TPhP in the eluate were measured to evaluate their adsorption at different DOM concentrations.
[0077] The C of TBEP, TCPP and TPHP under various dissolved organic matter (DOM) concentrations DGT / C soln The ratio concentration ranges are 0.82-0.91, 0.82-0.92 and 0.82-0.99 respectively. Fig. 9 The C values of different organophosphorus compounds measured by diffusion gradient thin film (DGT) technology at different DOM concentrations are shown. DGT / C soln Ratio. Fig.10 It can be seen that for the target OPEs, when the concentration of DOM increases in the range of 0 to 20 mg / L, their C DGT / C soln The ratios were stable between 0.82 and 0.99. This indicates that DOM had little effect on the adsorption of these compounds by NH2-HLB-DGT. The DGT measurements of the target organophosphates were independent of changes in DOM concentration.
[0078] 6. Determination and analysis of organophosphates in soil
[0079] Using GPS positioning, 16 soil samples were collected from a farmland in Hebei Province using the grid distribution method. The physical and chemical properties of the soil at the 16 sampling points were as follows: the soil pH range was 7.2-7.9, the maximum water holding capacity was 1.35, and the soil organic matter content was 11.2%.
[0080] To measure the TBEP, TCPP and TPhP contents in these soil samples, three different measurement methods were used: active sampling, the NH2-HLB-DGT method (experimentally prepared DGT device) and the LSLD-ATDGT method (commercially available DGT device for organophosphates in soils and sediments).
[0081] (1) Determination and analysis of organophosphates in soil using the DGT method
[0082] The DGT device prepared in the experiment and the DGT device available on the market for organophosphates in soil and sediment were used to determine the organophosphates in soil samples in the study area. The specific steps are as follows:
[0083] After air-drying the soil sample, sieve it through a 2mm sieve. Take 80g of soil and mix it with water to ensure that the moisture content reaches 60% of the maximum water capacity. After fully stirring, let the mixture stand for 2 days. Add water to the soil again to make the moisture content reach 80% to 100% of the maximum water capacity, and stir it again to make the soil surface flat. Place the treated soil in petri dishes of appropriate sizes according to experimental requirements, cover them with lids (leaving a certain gap), and let them stand for another 24 hours. When placing the soil, ensure that there is enough soil in a single petri dish so that after the DGT device is placed, there should be at least 1cm of space from the surface of the sampling window to the bottom of the petri dish. 4 to 6 hours before the experiment begins, take the DGT device out of the refrigerator to allow its temperature to reach equilibrium with the ambient temperature, apply the soil to the filter membrane of the DGT device, and then gently press it into the soil. During this process, the DGT device can be gently rotated left and right to ensure that the device is in full contact with the soil.
[0084] Throughout the experiment, accurately record the placement time (in minutes) of the DGT device in the soil and the temperature of the soil. When the soil temperature is approximately 20°C and the temperature fluctuation is within 2°C, the average temperature can be taken as the actual temperature during this period. After the experiment, the DGT device needs to be removed from the soil and rinsed with ultrapure water. Remove the filter membrane, diffusion membrane, and bottom adsorption membrane and place them in a 15mL brown glass bottle; add 10mL of HPLC-grade methanol for elution. Make sure that the adsorption membrane is completely immersed in the eluent, ultrasonicate the glass bottle for 30 minutes, and measure the concentration of organophosphates in the eluent.
[0085] (2) Determination and analysis of organophosphates in soil using active sampling method
[0086] OPEs were extracted from soil using ultrasonic extraction, and the specific steps are as follows: First, 3 g of soil was accurately weighed and placed in a 15 mL polypropylene tube, which was rinsed with n-hexane, acetone, and methanol in sequence before use to remove background interference. Subsequently, 4 mL of a methanol solution containing 0.5% ammonia (chromatographic grade, Fisherchemical, Waltham, MA, USA) was added to the tube and oscillated at 2000 rpm for 10 min to ensure adequate mixing. Next, ultrasonic extraction was performed for 30 min, and then centrifuged at 4000 rpm for 10 min to separate the supernatant from the soil. The extraction was repeated twice, and the supernatants of the two times were combined. The combined supernatant was evaporated to near dryness under nitrogen purge, and then 1 mL of methanol was added to make up the volume. After vortex mixing for 1 min, the sample solution was filtered through a 0.22 μm PTFE filter membrane into an injection vial for subsequent testing. The experiment used liquid chromatography-tandem mass spectrometry (LC-MS / MS, 4500, USA). The chromatographic column was Waters UPLC BEHC18 (size 100 mm × 2.10 mm, particle size 1.70 μm, USA), the ion source temperature was set to 600°C, the ionization voltage was 5000 V, the curtain gas was 25 psi, the spray gas and the auxiliary heating gas were 50 psi and 45 psi respectively, and the temperature of the chromatographic column was controlled at 40°C. The mobile phase included an inorganic phase A of 2 mmol ammonium acetate aqueous solution and an organic phase of methanol (chromatographic grade).
[0087] The measurement results showed that the contents of TBEP, TCPP and TPhP in soil samples measured by active sampling method were in the range of 0.46-51.53 μg / L, 0.002-0.09 μg / L and 0.0005-0.013 μg / L, respectively; the contents of TBEP, TCPP and TPhP in soil samples measured by prepared DGT were in the range of 0.31-0.52 μg / L, 0.14-1.60 μg / L and 0.014-0.036 μg / L, respectively; the contents of TBEP, TCPP and TPhP in soil samples measured by commercially available DGT were in the range of 0.025-0.70 μg / L, 0.089-5.47 μg / L and 0.002-0.05 μg / L, respectively.
[0088] In summary, NH2-HLB-DGT has better performance and higher stability. Compared with the commercially available DGT and soil active sampling method, it can more accurately determine the content of organophosphates in soil samples, which helps to improve the accuracy and efficiency of environmental monitoring.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An NH2-HLB composite adsorption membrane for adsorbing organic phosphates, characterized in that: The NH2-HLB composite adsorption membrane is prepared by adding a polymer formed by methanol-activated HLB resin and NH2 silica gel at a mass ratio of 6:4 to an agarose solution; The NH2-HLB composite adsorption membrane is used in a DGT device to detect the concentration of organic phosphates in a soil environment; The organic phosphate is one of TBEP, TCPP and TPhP.
2. The method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphate according to claim 1, characterized in that: The following steps are involved: (1) soaking the HLB resin in a methanol solvent for 30 minutes, washing with ultrapure water after solid-liquid separation, and obtaining a methanol-activated HLB resin; (2) soaking the NH2 silica gel in a methanol solvent for 30 minutes, and washing with ultrapure water after solid-liquid separation to obtain NH2 silica gel activated by methanol; (3) mixing the methanol-activated HLB resin with the methanol-activated NH2 silica gel to obtain an adsorption material; (4) mixing the adsorption material, agarose powder and ultrapure water, and heating to prepare an agarose solution; (5) The agarose solution was injected into the gap of a glass plate containing a 0.5 mm U-shaped Teflon sheet and solidified into a film to obtain an NH2-HLB composite adsorption film.
3. The method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphate according to claim 2, characterized in that: In the step (1), the mass volume ratio of HLB resin to methanol solvent is 4.5 g:6.3 mL.
4. The method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphate according to claim 2, characterized in that: In the step (2), the mass volume ratio of NH2 silica gel to methanol solvent is 3g:4.2mL.
5. The method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphate according to claim 2, characterized in that: In the step (3), the mass ratio of the methanol-activated HLB resin to the methanol-activated NH2 silica gel in the adsorption material is 6g:4g.
6. The method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphate according to claim 2, characterized in that: In the step (4), the mass volume ratio of the adsorption material, agarose powder and ultrapure water is 70g:10g:500mL.
7. The method for preparing an NH2-HLB composite adsorption membrane for adsorbing organic phosphate according to claim 2, characterized in that: In the step (5), the film forming temperature is 20±5° C., and the film forming time is ≥60 min.
Citation Information
Patent Citations
Method for detecting organophosphate in sediment
CN116642972A